Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.3 - Polynomial Functions, Graphs, and Composition - 4.3 Exercises - Page 296: 63



Work Step by Step

We are asked to find $(f∘g)(2)$. We know that $(f∘g)(x)=f(g(x))$. Therefore, $(f∘g)(2)=f(g(2))$. From the second table, we see that $g(2)=3$. From the first table, we see that $f(3)=1$. Therefore, $f(g(2))=f(3)=1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.